Universal Singular Public Space Design of the Early 21st Century - Curnier, Sonia (De Gruyter, 2022)
Critical introduction to the planning and design of public space. The design of public spaces is a reflection of their time. In our globalised world of images and experiences, however, the striving for uniqueness tends towards the opposite: square designs are becoming more and more similar in their choice of means and are thus becoming independent of their urban surroundings. The author analyses ten outstanding contemporary square designs in Europe with regard to their urban functionality and materialisation. In interviews with the planners, she traces the changes that the projects underwent during the planning phase and documents them with numerous sketches. She also examines the reception of these projects in the community. Translated with www.DeepL.com/Translator (free version)